Sex‐ and age‐specific effect of known type 2 diabetes mellitus on incident mild cognitive impairment five years later: Results from the population‐based Heinz Nixdorf Recall study - Anna Lena Platzbecker; Janine Gronewold; Sara Schramm; Susanne Moebus; Andreas Stang; Börge Schmidt; Christian Weimar; Martha Jokisch; the Heinz Nixdorf Recall Study Investigative Group (Alzheimer’s & Dementia: Diagnosis, Assessment & Disease Monitoring)
Abstract Introduction As studies on the association between type 2 diabetes mellitus (T2DM) and mild cognitive impairment (MCI), including amnestic (aMCI) and non‐amnestic (naMCI) subtypes, vary by sex and age, we investigated the sex‐ and age‐specific effects of T2DM on incident MCI after five years in a population‐based sample. Methods A total of 145 participants with T2DM and 1322 without T2DM were included. MCI was defined using established criteria excluding subjective cognitive decline. Adjusted relative risks (aRRs) were calculated considering age, education, body mass index, smoking, and alcohol intake, and stratified by sex and age (middle‐aged: 50–65 years; old‐aged: 66–80 years). Results MCI occurred in 39.3% (n = 57) of participants with T2DM versus 27.5% (n = 363) without (aRR: 1.29, 95% confidence interval [CI]: 0.97–1.73). Middle‐aged men showed an association with naMCI (aRR: 2.35, 95% CI: 1.26–4.39) and middle‐aged women with aMCI (aRR: 2.05, 95% CI: 0.58–7.21). Discussion T2DM increases MCI risk, particularly in middle‐aged individuals with poorly controlled T2DM, emphasizing the need for prevention strategies. Highlights Longitudinal results from the population‐based Heinz Nixdorf Recall study in Germany. Incident mild cognitie impairment (MCI) was more common in type 2 diabetes mellitus (T2DM; 39% vs 28%). T2DM affects incident MCI and subtypes in middle‐aged, not old‐aged; stronger in men with poorly controlled T2DM. Importance of enhancing age‐ and sex‐specific prevention at the population level.